Pengembangan Desa Wisata Pentingsari, Kabupaten Sleman dalam Perspektif Partisipasi Masyarakat - Wahyuni, Dinar (Jurnal Aspirasi, 2019)
Village tourism is one form of tourism that applies the concept of community empowerment so that community participation is the most important component in its development. This study aims to describe the development of the Pentingsari Tourism Village in the perspective of community participation. This research is descriptive with a qualitative approach. The results showed that the development  of  the  Pentingsari  Tourism  Village  received  full  support  from  the  Pentingsari  community and  local  government  through  its  participation  in  tourism  activities.  At  the  planning and  decisionmaking stages, the community participated from planning, socialization to community and village government, to making decisions about the formation of a tourism village. Community participation in the implementation phase is carried out by giving thought, material, and being directly involved in every tourism village development activity and trying to create a tourism village that is ready to compete in the tourism industry. Participation in the stage of enjoying the results is shown by improving the living conditions  of  the  Pentingsari  community  due  to  tourism  activities.  This  means  that  the  community  enjoys the results of tourism, economically, socially, culturally, and environmentally. Furthermore, community participation in the evaluation phase was demonstrated through their involvement in regular meetings between village tourism managers, village government and local government.AbtrakDesa  wisata  merupakan  salah  satu  bentuk  wisata  yang  menerapkan  konsep pemberdayaan  masyarakat  sehingga partisipasi  masyarakat  menjadi  komponen terpenting  dalam pengembangannya.  Penelitian  ini bertujuan untuk mendeskripsikan tentang pengembangan  Desa Wisata  Pentingsari  dalam  perspektif  partisipasi  masyarakat.  Penelitian  ini  bersifat  deskriptif dengan  pendekatan  kualitatif.  Hasil  penelitian  menunjukkan  bahwa  pengembangan  Desa Wisata Pentingsari  mendapat  dukungan penuh dari  masyarakat Pentingsari  dan  pemerintah  daerah  melalui partisipasinya  dalam  kegiatan wisata. Pada tahap  perencanaan  dan pengambilan  keputusan, masyarakat berpartisipasi mulai dari perencanaan,  sosialisasi ke masyarakat dan pemerintah  desa hingga pengambilan keputusan tentang  pembentukan  desa wisata. Partisipasi masyarakat  dalam tahap implementasi dilakukan dengan memberikan  pemikiran,  materi,  dan terlibat  langsung dalam setiap kegiatan pengembangan desa wisata serta berupaya menciptakan  desa wisata yang  siap  bersaing  di  industri  pariwisata.  Partisipasi  dalam  tahap  menikmati  hasil  ditunjukkan dengan peningkatan kondisi kehidupan masyarakat  Pentingsari akibat  kegiatan  wisata. Hal ini berarti bahwa masyarakat menikmati  hasil dari kegiatan  wisata baik secara ekonomi, sosial, budaya, dan lingkungan. Selanjutnya  partisipasi  masyarakat dalam  tahap  evaluasi  ditunjukkan melalui  keterlibatannya dalam  pertemuan  rutin antarpengelola  desa wisata, pemerintah  desa, dan pemerintah daerah setempat.